Respuesta :

The student messed up on step one. The proper factoring is (x-4) (x+2)

Answer:

B. in step 1

Step-by-step explanation:

Given that a student performed the following steps to find the solution of the quadratic equation [tex]x^2-2x-8=0[/tex].

Step 1: Factor the polynomial into (x-4) and (x-2).

Step 2: x-4=0 and x-2=0

Step 3: x=4 and x=2.

Now we need to find about which step has the error.

let's multiply (x-4) and (x-2)

we get : [tex](x-4)(x-2)=x^2-4x-2x+8=x^2-8x+8[/tex]

While original problem has -8 as the last term. So that means factors are wrong.

Hence choice B. in step 1. is correct